An Optimized Mouse Thigh Infection Model for Enterococci and its Impact on Antimicrobial Pharmacodynamics (2015)
Negligible in vivo growth of enterococci and high-level dispersion of data have led to inaccurate estimations of antibiotic pharmacodynamics (PD). Here we improved an in vivo model apt for PD studies by optimizing the in vitro culture conditions for enterococci. The PD of vancomycin (VAN), ampicillin-sulbactam (SAM), and piperacillin-tazobactam (TZP) against enterococci were determined in vivo, comparing the following different conditions of inoculum preparation: aerobiosis, aerobiosis plus mucin, and anaerobiosis plus mucin. Drug exposure was expressed as the ratio of the area under the concentration-time curve for the free, unbound fraction of the drug to the MIC (fAUC/MIC) (VAN) or the time in a 24-h period that the drug concentration for the free, unbound fraction exceeded the MIC under steady-state pharmacokinetic conditions (fT>MIC) (SAM and TZP) and linked to the change in log10 CFU/thigh. Only anaerobiosis plus mucin enhanced the in vivo growth, yielding significant PD parameters with all antibiotics. In conclusion, robust in vivo growth of enterococci was crucial for better determining the PD of tested antibacterial agents, and this was achieved by optimizing the procedure for preparing the inoculum.